Kajian Peran Tempat Istirahat (Rest Area) Kendaraan Guna Menurunkan Tingkat Kecelakaan Dan Kelelahan Pengemudi Pada Jalan Tol Ruas Jakarta-Cikampek - Setyabudi, Besar (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
gased on statistical data from PT Jasa Marga (Persero) Tbk. In 2010. Factor tops the driver's 1egligence caused the accident Jakarta-Cikampek toll road. A total of 1404 incidents in high:uay accidents caused by driver factor. because of lack of anticipation of the driver when the Jehicle in front will precede the 713 incidents, 620 incidents a sleepy driver, do not order 24 7Jents, 38 events off guard, and drunk six events and other three events. On the factors causng the accident vehicle tire that is 229 events, 67 events from tension brake, skid 51 incidents, )1 incidents of mechanical damage, damage to the engine 7 events and Iain seven events. ::reeways or highways, segments of Jakarta-Cikampek a way that can be traversed at high peed and is able to shorten the travel time of the middle density of public roads. However, this Jjten causes an accident that not a few lives. One contributing factor is fatigue and sleepiness as t travels away from the driver. rhe results of this study is gathering suggestions fram users abaut the existence of the highway rest rrea that can function both associated with a reduction in toll road accident rate and its facilities fesired by the driver when they are in the resting place of the vehicle after releasing tired vehicles. Keywords: Rest, Fatigue, Driver